1991
DOI: 10.1128/mcb.11.2.677
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interactions between transcription factors control expression of the apolipoprotein AI gene in liver cells.

Abstract: The gene coding for apolipoprotein Al (apoAl), a plasma protein involved in the transport of cholesterol and other lipids in the plasma, is expressed predominantly in liver and intestine. Previous work in our laboratory has shown that different cis-acting elements in the 5'-flanking region of the human apoAl gene control its expression in human hepatoma (HepG2) and colon carcinoma (Caco-2) cells. Hepatocyte-specific expression is mediated by elements within the -256 to -41 DNA region relative to the apoAl gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 55 publications
(42 reference statements)
6
92
0
1
Order By: Relevance
“…A CAT is a slightly stronger promoter than its G counterpart (72.4% vs. 62% of awtylation). Altion factors identified [21,23]. The deletion studies have most identical results were obtained when the two other shown previously [13] that the apo A?…”
Section: Resultssupporting
confidence: 70%
“…A CAT is a slightly stronger promoter than its G counterpart (72.4% vs. 62% of awtylation). Altion factors identified [21,23]. The deletion studies have most identical results were obtained when the two other shown previously [13] that the apo A?…”
Section: Resultssupporting
confidence: 70%
“…To construct pREϫ4-E4T and pREϫ4-MLT, a double-stranded oligonucleotide containing four tandemly repeated copies of the HNF4␣-responsive element from the apolipoprotein A-I enhancer element (TGAACCCTTGACCCCTGC) (50,51) was introduced between the PstI and BamHI sites of pG5-E4T and pG5-MLT (52). The BamHI site is located 13 or 27 bp upstream of the TATA boxes of the adenovirus major late (AdML) or E4 core promoter, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Hep G2 liver cells and Caco-2 intestinal cells were transfected with the plasmid pA1·474.CAT, which carries the full sequence of rat apoAI gene promoter, along with the CAT reporter gene (Widom et al 1991, Romney et al 1992, Taylor et al 1996, Mooradian et al 1997, Harnish et al 1998, Murao et al 1998. Both of these cell lines are suitable for these studies since they express the endogenous apoA1 gene (see below).…”
Section: Effect Of Ketone Bodies On the Apoa1 Gene Promotermentioning
confidence: 99%